A Textual Edition of Donne's "The Cross" and the Implications of Establishing a Copy-text - Lake, Danielle M. (East Carolina University, 2015)
This thesis provides a copy-text for John Donne's poem "The Cross" based on all extant manuscript evidence. The first section is an introduction to the entire project. The second section of the thesis presents the rationale for the copy-text (an emended version of WN1), including the textual introduction, stemma, stemma notes, and textual apparatus. The third section contains a literary analysis of the poem. The textual introduction and stemma show how the 17th-century artifacts--including manuscript and printed sources--circulated and how these texts relate to one another.   The third and final section provides a literary analysis of "The Cross." This portion begins with a discussion of the most signifant scribal variants found in printed editions, including the change from "call" to "all" in line 48, "Poynts" to "Pants" in line 52, and "fruitefullye" to "faithfully" in line 61. The "Literary Analysis" portion also explores two gaps in scholarship: Donne's unnoted witty syntax in the poem and an unnoticed connection between "The Cross" and Donne's 1622 Hanworth Sermon.
Keywords: British and Irish literature; Donne Variorum; Editing; Manuscripts; Cross, The; Variorum edition of the poetry of John Donne; Donne, John, 1572-1631--Criticism, Textual; Donne, John, 1572-1631. Cross--Criticism, Textual; Discourse analysis, Literary